2018
DOI: 10.1142/s0218348x18400017
|View full text |Cite
|
Sign up to set email alerts
|

Size Effect on the Permeability and Shear Induced Flow Anisotropy of Fractal Rock Fractures

Abstract: The effect of model size on fluid flow through fractal rough fractures under shearing is investigated using a numerical simulation method. The shear behavior of rough fractures with selfaffine properties was described using the analytical model, and the aperture fields with sizes ¶ Corresponding author. This is an Open Access article published by World Scientific Publishing Company. It is distributed under the terms of the Creative Commons Attribution 4.0 (CC-BY) License. Further distribution of this work is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Moreover, the size-dependence of hydraulic properties is a critical problem in correlating the laboratory-scale investigations to in-situ applications. Before applying the results of laboratory-scale investigations to field-scale predictions, the scaling effect in hydraulic properties and their relationships must be addressed (Matsuki et al 2006;Singh et al 2016;Huang et al 2018;Sawayama et al 2021;Zhong et al 2021). Accordingly, this has led to efforts to address the size-dependency of fluid flow through fractured rock and to determine the corresponding optimum specimen size above which the apparent size effect is no longer important (Witherspoon et al 1979;Witherspoon 1981).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the size-dependence of hydraulic properties is a critical problem in correlating the laboratory-scale investigations to in-situ applications. Before applying the results of laboratory-scale investigations to field-scale predictions, the scaling effect in hydraulic properties and their relationships must be addressed (Matsuki et al 2006;Singh et al 2016;Huang et al 2018;Sawayama et al 2021;Zhong et al 2021). Accordingly, this has led to efforts to address the size-dependency of fluid flow through fractured rock and to determine the corresponding optimum specimen size above which the apparent size effect is no longer important (Witherspoon et al 1979;Witherspoon 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Although fractures in rock masses are typically present in interconnected networks, the behavior of the fluid in a single fracture must be understood first before more complicated field-scale fracture networks can be addressed (Merrill 1975;Brown 1987;Pyrak-Nolte et al 1988;Hakami and Larsson 1996;Brown et al 1998;Zimmerman and Yeo 2000;Konzuk and Kueper 2004;Xiong et al 2011;Zhang and Nemcik 2013;Javadi et al 2014;Huang et al 2018;Cao et al 2019;Zhang et al 2019). As one of the common approaches, the rock core contains an artificially created or a natural fracture that is used for laboratory investigations, where the fluid flow in the single fracture can be investigated under controlled conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The larger the JRC value is, the rougher the surfaces are[9]. Many studies have shown that the aperture of fractures usually obeys a normal distribution[20,49]. According to the obtained apertures, Gaussian fitting was performed on the aperture of each fracture model.…”
mentioning
confidence: 99%